2021
DOI: 10.3390/genes12081171
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle-Derived DNA vs. CfDNA as a Biomarker for the Detection of Colon Cancer

Abstract: Liquid biopsy has emerged as a promising non-invasive way to diagnose tumor and monitor its progression. Different types of liquid biopsies have different advantages and limitations. In the present research, we compared the use of two types of liquid biopsy, extracellular vesicle-derived DNA (EV-DNA) and cell-free DNA (cfDNA) for identifying tumor mutations in patients with colon carcinoma. Method: DNA was extracted from the tumor tissue of 33 patients diagnosed with colon carcinoma. Targeted NGS panel, based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In contrast to our results, Bryzgunova and collaborators demonstrated that EVs of urine samples from patients with prostate cancer presented higher DNA concentrations than healthy samples [ 36 ], although these variances could be attributed to the different type of sample and cancer from which EVs were isolated. Despite this, DNA from EVs can be studied [ 31 ], and our results indicate a sufficient concentration of DNA for use, as shown in studies by Thakur and collaborators, who found that DNA concentration in serum EVs was 10.59 ± 13.19 ng/mL [ 37 ], or in studies by Choi et al, who determined that the amount of DNA in plasma EVs ranged from 0.1 to 2.48 ng [ 38 ]. Finally, protein expression levels can be directly determined in BLF samples, as shown in studies by Kayazawa and collaborators, in which lactoferrin, polymorphonuclear neutrophil elastase, myeloperoxidase, and lysozyme concentrations were determined in BLF samples by ELISA [ 39 ].…”
Section: Discussionmentioning
confidence: 51%
“…In contrast to our results, Bryzgunova and collaborators demonstrated that EVs of urine samples from patients with prostate cancer presented higher DNA concentrations than healthy samples [ 36 ], although these variances could be attributed to the different type of sample and cancer from which EVs were isolated. Despite this, DNA from EVs can be studied [ 31 ], and our results indicate a sufficient concentration of DNA for use, as shown in studies by Thakur and collaborators, who found that DNA concentration in serum EVs was 10.59 ± 13.19 ng/mL [ 37 ], or in studies by Choi et al, who determined that the amount of DNA in plasma EVs ranged from 0.1 to 2.48 ng [ 38 ]. Finally, protein expression levels can be directly determined in BLF samples, as shown in studies by Kayazawa and collaborators, in which lactoferrin, polymorphonuclear neutrophil elastase, myeloperoxidase, and lysozyme concentrations were determined in BLF samples by ELISA [ 39 ].…”
Section: Discussionmentioning
confidence: 51%
“…In turn, Thakur et al reported similar detection rates when using either circulating EV-DNA or cfDNA for the identification of several mutations in CRC patients [109]. In the future, however, a combination of both EV-derived nucleic acids and cfDNA might represent the most efficient procedure for non-invasive cancer-associated mutation screenings [110,111]. This approach was also applied for the development of a clinical test developed by Exosomes Diagnostics (ExoDx Lung(EGFR T790M)), which efficiently identified different EGFR mutations (L858R, T790M, and exon 19 indels) in plasma sEVs from a large cohort of non-small cell lung carcinoma (NSCLC) patients [112].…”
Section: Ev-associated Dna For Mutation Screeningsmentioning
confidence: 97%
“…The most widely used tools are circulating tumor cells (CTC) and cell-free DNA (cfDNA) (1)(2)(3). Extracellular vesicle (EV) DNA (EV-DNA) has recently emerged as informative cancer biomarker (4)(5)(6)(7)(8). EVs constitute a diverse and heterogeneous category of vesicles released by every cell type.…”
Section: Conclusion: Ev-dna Extraction and Sequencing In Old Serum Sa...mentioning
confidence: 99%